Patient-reported outcome measures in rehabilitation after knee surgery: a rapid systematic review - Moreira, José (2024)
Aim: Musculoskeletal conditions impact our society owing to the associated burden, with significant implications for health systems and people’s quality of life. Patient-reported outcome measures (PROMs) are used to optimize the results of rehabilitation programs. The study aims to identify the PROMs used in rehabilitation programs after knee surgery. Subject and methods: This rapid systematic review was conducted using MEDLINE® and CINAHL® databases, considering all studies carried out until December 2023, with a registered protocol (PROSPERO reference: CRD42024504263). Studies were included with adult participants undergoing knee surgery and using PROMs to measure outcomes before and after rehabilitation programs. Results: Sixteen studies with 3469 participants in rehabilitation programs after knee surgery were included. Methodologically and according to the criteria recommended by the Joanna Briggs Institute, more than half of the studies were of high quality, with values of more than 80%, including randomized controlled trials, cohorts, and quasi-experimental designs. Outcomes were assessed before and after rehabilitation programs, using general (n = 6) and knee-specific (n = 11) PROMs. Of all the PROMs identified in the different studies selected for this systematic review, the ones used the most were KOOS (in 14 studies), EQ5D-5L, and WOMAC (in 3 studies). Conclusion: This rapid systematic review shows the need to identify and implement PROMs during rehabilitation programs after knee surgery, measuring participants’ health status, symptoms, treatment satisfaction, and physical and mental performance. In this way, it is possible to make value-based comparisons with other interventions, improving and tailoring rehabilitation care.